Germany’s attitude towards the enlargement of the eurozone - Płóciennik, Sebastian (Economics and Business Review, 2021)
The purpose of this paper is to answer the question as to why Germany is cautious towards a faster enlargement of the euro area. The usual explanation focuses on concerns that some of the candidate countries are not economically ready to adopt the common currency and their membership could destabilize the monetary union. However, such an approach does not take into account other factors that may influence Germany’s reluctance to speed up the enlargement process. One of them is the conviction that the existing division of integration does not translate into economic costs and a long-term political cleavage in the EU. Another argument explaining Germany’s position is their doubt about the economic policy preferences of the candidates which may prove to be crucial in the upcoming reform of the euro area governance. Some of them can drift towards more interventionism and support for the debtors’ positions which is at odds with German interest.